Advanced high strength natural fibre composites in construction - Fan, Mizi; Fu, Feng (Structural engineer) (Woodhead Publishing series in composites science and engineering ;, 2017)
Advanced High Strength Natural Fibre Composites in Construction provides the basic framework and knowledge required for the efficient and sustainable use of natural fiber composites as a structural and building material, along with information on the ongoing efforts to improve the efficiency of use and competitiveness of these composites. Areas of particular interest include understanding the nature and behavior of raw materials and their functional contributions to the advanced architectures of high strength composites (Part 1), discussing both traditional and novel manufacturing technologies for various advanced natural fiber construction materials (Part 2), examining the parameters and performance of the composites (Part 3), and finally commenting on the associated codes, standards, and sustainable development of advanced high strength natural fiber composites for construction. This exposition will be based on well understood environmental science as it applies to construction (Part 4). The book is aimed at academics, research scholars, and engineers, and will serve as a most valuable text or reference book that challenges undergraduate and postgraduate students to think beyond standard practices when designing and creating novel construction materials.